Agenda for a new economy from phantom wealth to real wealth - Korten, David (San Francisco Berrett-Koehler, 2010)
Nearly two years after the economic meltdown, joblessness and foreclosures are still endemic, Wall Street executives are once again getting massive bonuses, and our leaders in Washington lack the will to make desperately needed fundamental changes to the economy. Change will have to come from below. Agenda for a New Economy is the handbook for that revolution.
Includes bibliographical references (p. 285-295) and index.
Keywords: Wealth -- United States; United States -- Economic policy